Inside Back Cover: Applications and regulatory of nanotechnology‐based innovative in vitro diagnostics (View 2/2021). Issue 2 (8th April 2021) - Chen, Kuan; Han, Houyu; Tuguntaev, Ruslan G.; Wang, Peirong; Guo, Weisheng; Huang, Jiayu; Gong, Xiaoqun; Liang, Xing‐Jie
Abstract : In article number 20200091, Xing‐jie Liang, Xiaoqun Gong, Kuan Chen and co‐workers display that nanotechnology‐based in vitro diagnostics (nanoIVDs) are widely studied for disease diagnostics with promising sensitivity, specificity and convenience. However, it is still a major challenge for both regulatory authorities and scientific researchers to accelerate the clinical translation of nanoIVDs. Herein, they discussed the benefits and challenges of nanoIVDs as well as the administration considerations on the distinguish features of nanoIVDs by regulatory authorities, so as to further achieve the evaluation, translation and application of nanoIVD products.